Hypoglycemic and hypolipidemic activity of aqueous extract of Ficus racemosa seeds - Urmi, Kaniz Fatima; Haque, Afroza; Hamid, Kaiser; Ullah, M Obayed; Howlader, Md. Amran; Hossain, Md. Afjal (Pharmacognosy Communications)
Introduction: The incidence of diabetes mellitus is on rise all over the world. Moreover the synthetic drugs are likely to give serious side effects. That is why the expert committee on diabetes at WHO recommends the screening of medicinal plants for the management of diabetes. Objective: The present study was designed to investigate the hypoglycemic and hypolipidemic potential of F. racemosa seeds in streptozocin (STZ) induced diabetic mice. Materials and Methods: Swiss albino mice of both sexes, aged 7-8 weeks, average weight of 20-30 gm were used for the experiments. Animals were treated with aqueous extract of F. racemosa seeds at a dose of 200 mg/kg body weight. Blood glucose, triglycerides, LDL, HDL and cholesterol was measured at the beginning and end of the experiment. Results: Blood glucose and other studied parameters were elevated in the diabetic mice and were brought about near to the control group (except HDL) by the aqueous extract of F. racemosa seeds (200 mg/kg body weight). The decrease in all the parameters (except HDL) were statistically significant (P < 0.001). Conclusion: The present study suggests that the aqueous extract of F. racemosa seeds can be used for further isolation and identification of active principles with hypoglycemic and hypolipidemic potential.
Keywords: F. racemosa seeds; diabetes; streptozocin (STZ); hypoglycemic; hypolipidemic